UNPACKING THE HIERARCHICAL DIMENSIONS OF COMMUTE COST RESILIENCE: EVIDENCE FROM CONSTRUCTION WORKERS - Mitchell, Dr. Emily Anne; Zhang , Prof. Wei Jun; Turner , Dr. Benjamin Michael (International Journal of Allied Research in Economics (IJARE), 2024)
This paper delves into the philosophical and economic conceptualizations of ends and means, scrutinizing their inherent nature and categorization. The assertion is made that ends inherently pertain to the subjective realm, while means are firmly situated in the objective domain. Within the subjective sphere, human wants and needs are considered, and further dissected through the lens of Maslow’s hierarchy, delineating a hierarchical structure. However, in contrast, resources and means resist hierarchical division akin to Maslow’s hierarchy of needs. Specifically, transportation, identified as a subset of means/resources, challenges the appropriateness of applying the theory of Transportation System Users’ Hierarchy of Needs, as posited by Sun and Philips in 2020.